2022
DOI: 10.3390/ijms23073731
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of BLH Transcription Factors in Plant Development and Environmental Response

Abstract: Despite recent advancements in plant molecular biology and biotechnology, providing enough, and safe, food for an increasing world population remains a challenge. The research into plant development and environmental adaptability has attracted more and more attention from various countries. The transcription of some genes, regulated by transcript factors (TFs), and their response to biological and abiotic stresses, are activated or inhibited during plant development; examples include, rooting, flowering, fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…Populus alba × P. glandulosa KNOX subfamily member PagKNAT2/6b can mediate drought response by down-regulating PagGA20ox1 gene of GA pathway (Song et al, 2021). Similarly, the expression of TALE genes is not only regulated by hormones, but also affected by abiotic stress (Tsuda and Hake, 2015;Niu and Fu, 2022). The promoters of TALE gene family members in soybean contained cis-elements that responded to various stresses, and the expression level of GmTALE gene could change in response to salt stress and drought stress (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populus alba × P. glandulosa KNOX subfamily member PagKNAT2/6b can mediate drought response by down-regulating PagGA20ox1 gene of GA pathway (Song et al, 2021). Similarly, the expression of TALE genes is not only regulated by hormones, but also affected by abiotic stress (Tsuda and Hake, 2015;Niu and Fu, 2022). The promoters of TALE gene family members in soybean contained cis-elements that responded to various stresses, and the expression level of GmTALE gene could change in response to salt stress and drought stress (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the TALE gene family is involved in plant hormone regulatory pathways (Tsuda and Hake, 2015;Niu and Fu, 2022). The exogenous hormone application showed that the expression of KNOX gene family members of Caucasian clover could respond to the changes of 6-BA, IAA, and KT signals (Zhang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors play an important role in plant development and stress response ( Niu and Fu, 2022 ). In this study, the DEGs affected by STS in the AZ of rose petals included a large number of TFs.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between POX and MEINOX is hydrophobic (Ezura et al 2022). The interaction of them affects phytohormone regulation that is related to plant development (Niu & Fu 2022). The heterodimer modulates phytohormone by activating cytokinin and repressing gibberellin (Tadege 2013;Testone et al 2015;Marsch-Martínez & de Folter 2016), which correlates to shoot development (Wybouw & De Rybel 2019;Arro et al 2019).…”
Section: Protein Modelling Of Poh1 Protein and Its Domain Functionmentioning
confidence: 99%